Statefinder and Om Diagnostics for New Generalized Chaplygin Gas Model - Abdulla Al Mamon; Vipin Chandra Dubey; Kazuharu Bamba (Universe, 2021)
We explore a unified model of dark matter and dark energy. This new model is a generalization of the generalized Chaplygin gas model and is known as a new generalized Chaplygin gas (NGCG) model. We study the evolutions of the Hubble parameter and the distance modulus for the model under consideration and the standard <semantics>Λ</semantics>CDM model and compare that with the observational datasets. Furthermore, we demonstrate two geometric diagnostics analyses including the statefinder <semantics>(r,s)</semantics> and <semantics>Om(z)</semantics> to the discriminant NGCG model from the standard <semantics>Λ</semantics>CDM model. The trajectories of evolution for <semantics>(r,s)</semantics> and <semantics>Om(z)</semantics> diagnostic planes are shown to understand the geometrical behavior of the NGCG model by using different observational data points.